KEARIFAN TRADISI ISLAM DALAM PENGELOLAAN AIR - Alfalisyado Alfalisyado (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
This article discuss and analyze about concept and characteristicof water in Islam. This concept influences to the social and economic aswell. Beside, this article describe about concept of water transformationand changing of society point of view, partly and globally. These data arecollected by text and context study, especially by the mix approach, it’sculture study and Islamic jurisprudence. The result of this study, there isshifting of understanding in Islamic scholars about concept of water functionfrom al-miyah al-fit}rah (water as a natural function) to al-miya>h aliqtis}a>diyyah (commercial water).